Hernia of the umbilical cord: a clinical spectrum - Patole, Monali Madhukar; Patole, Mandar Madhukar; Paul, Subhasish (International Journal of Contemporary Pediatrics, 2019)
Background: Hernia of the umbilical cord is a rare clinical entity which presents with hernia of the small bowel into the proximal part of the umbilical cord. This is sporadically associated with other congenital malformations. This is usually poorly identified and mistakenly termed as ‘omphalocele minor. Inadvertent clamping of the cord in these cases leads to iatrogenic bowel wall injury. The aim of this study is to present a spectrum of cases presenting with umbilical cord hernia in a tertiary care Govt medical college, along with demography, intra operative findings, associated malformations and postoperative outcome and 1 year follow up. Methods: This is an ambispective study on neonates who attended the Outpatient Department (OPD) or Emergency department. The babies were evaluated by age, birth weight, gender, any gross clinical malformation. They were also evaluated intraoperatively for any associated anomalies. Post-surgery the babies were followed up until 2 years of age in pediatric surgery OPD of the same institute and outcome was recorded. Results: Out of 90 babies, 88 babies (97.77%) had body weight more than 2.5 kg, and rest 2(2.22%) had bodyweight of 1.5kg and 1.8 kg. Regarding content of contents of umbilical cord hernia, out of 87 patients, 43 patients (49.42%) had ileal loop as, 32 patients (36.78%) had ileum with Meckel’s diverticulum, 6 patients (6.39%) had cecum with appendix. Conclusions: Most of this study cases had ileal loops as content of the hernial sacs, and 36.78% cases had Meckel’s diverticulum associated, which is a remnant of Vitello intestinal duct. Prompt identification of the condition and early intervention and adequate post-natal care are affective to prevent long term morbidity.